Potential of Exserohilum Monoceras (Drechsler) Leonard and Suggs Isolated from Echinochloa P. Beauv. Species as a Bioherbicide - Sadi, Tosiah (2010)
Echinochloa spp is widespread in the warm temperate, sub tropical and tropical regions. It is ubiquitous in the Malaysia rice fields and serious weedy pest to the crop, especially after the adoption of double cropping, more rapidly maturing cultivars and a shift from transplanting to direct sowing. The problem worsens by the contamination of farm machineries such as tractors and combined harvester and also through seeds contamination. Chemical herbicides are widely used to control the grass which has a negative implication to the environment and public health. Several fungal pathogens have been reported to be potential biocontrol agents of this weed. This study was conducted to identify potential indigenous fungal pathogens for the control of Echinochloa spp and its requirements to be developed as bioherbicide. Exserohilum monoceras isolate 1125 was identified to be the potential fungus to control Echinochloa spp. Studies on the efficacy of the fungus indicated that it was effective at concentration of 10 6 spores/mL, and plant was sensitive at their 4 leaves stage. The fungus attacked E. crus-galli var crus galli, E. crus-galli var formosensis, E.colona and E. orizycola but with different disease intensity. The fungus was safe to all modern rice varieties, turf grasses and the selected vegetable crops tested, indicated that it was highly selective. Before it developed into a bioherbicide, the fungus need to mass produced. This study indicated that carbon source enhance, mycelium and production also disease efficacy. Addition of Nitrogen source does not increase the mycelium production however the spore production was significantly increased. The CN ratio found to be good for the mycelium and spore production range from 9:1 to 24:1. Exserohilum monoceras infection was influence by availability of dew and temperature. The fungus needed a minimum 12 hrs of humidity to caused severe disease on the host. The best temperature for infection is within the range 25OC to 35OC. Exserohilum monoceras was also effective in field condition. Spore concentration at the rate of 106 spore/mL and 107 spore/mL produced 45% and 50% control of Echinochloa in the field respectively. At the rate 108 spore/mL the fungus caused toxic effect on rice plants but recovered after sometimes. Disease severity also increased with spray frequency. The apparent infection rate at 107 spore/mL (rL = 0.14 logit/day) was highest followed by 108 spore/mL (rL = 0.13 logit/day) and 106 spore/mL (rL =0.12 logit/day). At the end of the trial, tillers production and dry weight of Echinochloa was also reduced. The result of this research indicated that E. monoceras has potential as a candidate for bioherbicide in the control of Echinochloa in rice field but need some improvement in the formulation.